PENGARUH PELATIHAN KONTROLDIRI DENGAN MENGGUNAKAN METODETEHNIK GERAKAN MENGONTROL PERILAKU MEROKOK (TGMPM) UNTUK MENGURANGIPERILAKU MEROKOK PADA SISWA SMK HARAPAN KARTASURA - Nurjanah, Maslichah Raichatul (TALENTA, 2014)
Smoking behavior is behavior that is dangerous to health so that on every pack of cigarettes and cigarette advertisements are required to include the dangers of smoking . However, the dangers of smoking behavior seems not too reduce interest teenagers to smoke . Data from the WHO shows that 30 % of smokers are young people , 24% of young men in Indonesia smoke . Surveys conducted in vocational Hope Kartasura showed that 71 % smoked , and 60 % smoked because the invitation of friends . Based on these facts , the self-control training is expected to reduce the smoking behavior of students . Among the number who smoke , most started smoking intheir teens , one of the psychological aspects that influence adolescent smoking or not smoking is self-control . Adolescents with high self-control will be able to copewith the pressure to smoke . This study aims to determine the effectiveness of self-control training using the Smoking Control Movement Technique ( SCMT ) to reduce smoking behavior in students of SMK Harapan Kartasura . This study was conducted experiment with Completely Randomized Design design - Between subjec . Subjects numbered 10 students consisting of 3 students who have low smoking behavior , 4 people who have smoking behavior was and 3 students who have high smoking behavior . Measuring instrument used was a questionnaire Smoking Behavior , interviews , observation , and self-control training module using the Smoking Control Movement Emotional Technique ( SCMT ) . Measurements were taken before and after training . Hypothesis test used was the Wilcoxon test for the pretest and posttest . The results of this study showedno significant effectbetween self-control training using the Smoking Control Movement Emotional Technique ( SCMT ) to reduce smoking behavior . Training self control when applied to smoking behavior and low groups were obtained effective results , but when applied to the smoking behavior of high group obtained results ineffective .